PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN SIKAP TOLERANSI - Ahmad Yury Alam F; Magfirotul Fatkha; Iis Kurnia (Universitas Islam Depok, 2023)
This study aims to describe: (1) the efforts of Islamic Religious Education teachers in internalizing the values ​​of tolerance between religious students at SMAN 1 Petir. (2) The supporting and inhibiting factors of Islamic Religious Education teachers in instilling an attitude of religious tolerance in students at SMAN 1 Petir. This research uses the type of research conducted in the field or field research (field research). The approach used in this research is a qualitative approach. Data sources include: (1) Primary data sources namely school principals, Islamic religious education teachers and students at SMAN 1 Petir (2) Secondary data sources namely documents or archives that support religious tolerance and other supporting data. Data collection techniques through observation, interviews (interviews) and documentation. The data analysis method uses three steps, namely data reduction, data presentation and verification.